Factors associated to academic procrastination in dental students from seven Cuban universities - Ibraín Enrique Corrales-Reyes; Mónica García-Raga; José Daniel Villegas-Maestre; Leonardo Valdés-Gamboa; Adrián Alejandro Vitón-Castillo; Diana Tusell-Hormigó; Christian R. Mejia (Revista Cubana de Medicina Militar, 2022)
Introduction: Procrastination, which is the action of postponing certain activities, has a negative impact on the academic field, hence the need to investigate the subject. Objective: To determine some factors associated with academic procrastination in Cuban dental students. Methods: Multicenter, observational, analytical and cross-sectional study, performed in 7 Cuban universities. Procrastination was investigated with a validated scale and adjusted prevalence ratios (aPR), 95 % confidence intervals (95 % CI), and p-values were obtained using generalized linear models. Results: Of the 738 students, 17 % and 14 % put off course work and reading that they don't like; respectively. In the multivariate model, it was found that being older (aPR: 1,16; 95 % CI: 1,05-1,29; p= 0,003) and having the support of a tutor (aPR: 1,81; 95 % CI: 1,24-2,64; p= 0,002) were factors associated with a higher frequency of procrastination. On the contrary, there was less procrastination among those who had published at least one scientific article (aPR: 0,62; 95 % CI: 0,40-0,97; p= 0,036); adjusted for 3 variables. Conclusions: Age, having a tutor and the publication of scientific articles were factors associated with academic procrastination in Cuban dental students.